2019
DOI: 10.1001/jamaophthalmol.2018.6906
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Spectacle Wear and Reasons for Nonwear in Students Randomized to Ready-made or Custom-made Spectacles

Abstract: IMPORTANCEVisual impairment from uncorrected refractive errors affects 12.8 million children globally. Spectacle correction is simple and cost-effective; however, low adherence to spectacle wear, which can occur in all income settings, limits visual potential.OBJECTIVE To investigate predictors of spectacle wear and reasons for nonwear in students randomized to ready-made or custom-made spectacles. DESIGN, SETTING, AND PARTICIPANTSIn planned secondary objectives of a noninferiority randomized clinical trial, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 43 publications
1
30
0
Order By: Relevance
“…A study of 7681 students aged 5 to16 years in rural Yunan of China found that among the students who needed glasses, only 18.9% owned them [18], which is lower than the study in urban (35.3%) [19] and rural (61.2%) China [20]. The reasons underlying low spectacles wearing among myopia might be multifactorial, including the lack of screening for detecting myopia, teasing or bullying by peers, the low attention and consciousness of the need for glasses, or the mis-conception by parents or students that wearing glasses will make the myopia worse [1921]. A recent study found that the teasing or bullying by peers (48.6%) and the lost or forgot or stolen spectacles (26.1%) are the major reason of not wearing the prescribed glasses [21].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…A study of 7681 students aged 5 to16 years in rural Yunan of China found that among the students who needed glasses, only 18.9% owned them [18], which is lower than the study in urban (35.3%) [19] and rural (61.2%) China [20]. The reasons underlying low spectacles wearing among myopia might be multifactorial, including the lack of screening for detecting myopia, teasing or bullying by peers, the low attention and consciousness of the need for glasses, or the mis-conception by parents or students that wearing glasses will make the myopia worse [1921]. A recent study found that the teasing or bullying by peers (48.6%) and the lost or forgot or stolen spectacles (26.1%) are the major reason of not wearing the prescribed glasses [21].…”
Section: Discussionmentioning
confidence: 92%
“…The reasons underlying low spectacles wearing among myopia might be multifactorial, including the lack of screening for detecting myopia, teasing or bullying by peers, the low attention and consciousness of the need for glasses, or the mis-conception by parents or students that wearing glasses will make the myopia worse [1921]. A recent study found that the teasing or bullying by peers (48.6%) and the lost or forgot or stolen spectacles (26.1%) are the major reason of not wearing the prescribed glasses [21]. Thus, education on students and parents about the importance of timely screening for myopia and wearing glasses for best vision is very important to improve student learning and academic achievement.…”
Section: Discussionmentioning
confidence: 99%
“…20 The reasons underlying low spectacles wearing among myopia might be multifactorial, including the lack of screening for detecting myopia, teasing or bullying by peers, the low attention and consciousness of the need for glasses, or the mis-conception by parents or students that wearing glasses will make the myopia worse. [19][20][21] A recent study found that the teasing or bullying by peers (48.6%) and the lost or forgot or stolen spectacles (26.1%) are the major reason of not wearing the prescribed glasses. 21 Thus, education on students and parents about the importance of timely screening for myopia and wearing glasses for best vision is very important to improve student learning and academic achievement.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] A recent study found that the teasing or bullying by peers (48.6%) and the lost or forgot or stolen spectacles (26.1%) are the major reason of not wearing the prescribed glasses. 21 Thus, education on students and parents about the importance of timely screening for myopia and wearing glasses for best vision is very important to improve student learning and academic achievement.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that the two trial arms were not balanced for VA at baseline. From previous research we know that poorer presenting VA is a predictor of spectacle wear [35] and we undertook post hoc analysis that stratified the risk difference of spectacle wear by baseline VA.…”
Section: Methodsmentioning
confidence: 99%